Management : challenges in the 21st century - Lewis, Pamela S. (South-Western College, 2001)
This book is about: Meeting the challenges of the 21st century; Planning challenges in the 21st century; Organizing challenges in the 21st century; Leadership challenges in the 21st century; ...